2013
DOI: 10.2478/bvip-2013-0087
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of Mycoplasma bovis in experimentally infected calves

Abstract: The effect of three different field isolates of Mycoplasma bovis on selected immunological parameters in experimentally infected calves was studied. Calves were kept separately in 4 experimental groups, and animals of 3 groups were infected intratracheally with one of the three selected isolates of M. bovis. The control group was inoculated intra-tracheally with sterile physiological saline. Nasal swabs and blood samples were collected just before the calf inoculation, then daily for seven days, and then weekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
(19 reference statements)
3
13
0
1
Order By: Relevance
“…In Groups E2 and E3, there was a lack of a distinct B-cell response, although the response was more marked for the E2 calf pneumonia isolate where increases in the WC4 + percentage were observed on days 14 and 28. In this study, the course of the B-cell response could be associated with the production of specific antibodies to M. bovis which were detected in our previous study in the experimental calves from day 21 for Group E2 and from day 14 for Group E3 (Dudek et al, 2013). In contrast, the WC4 + count increase was generally stimulated in the calves inoculated with the E1 mastitic isolate and specific antibodies to M. bovis were detected from day 21.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…In Groups E2 and E3, there was a lack of a distinct B-cell response, although the response was more marked for the E2 calf pneumonia isolate where increases in the WC4 + percentage were observed on days 14 and 28. In this study, the course of the B-cell response could be associated with the production of specific antibodies to M. bovis which were detected in our previous study in the experimental calves from day 21 for Group E2 and from day 14 for Group E3 (Dudek et al, 2013). In contrast, the WC4 + count increase was generally stimulated in the calves inoculated with the E1 mastitic isolate and specific antibodies to M. bovis were detected from day 21.…”
Section: Discussionsupporting
confidence: 52%
“…Previously Dudek et al (2013) used a similar experimental design which demonstrated the immunomodulatory effect of M. bovis in calves. In response to that M. bovis infection both a stimulation and a suppression of immunity in the affected calves was observed, depending on the mycoplasma isolate used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations